Adaption of tendon connective tissue to exercise - implications for training and injury in alpine skiing - Kjaer, M.; Langberg, H.; Dossing, S.; Holm, L.; Hansen, M.; Heinemeier, K.; Hansen, P.; Schjerling, P.; Hassenkam, T.; Magnusson, P. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Acute and chronic injuries both in alpine skiing and other sports often affect the connective tissue in the form of acute rupture of ligaments or tendons, or overuse injury of the tendon tissue. Rather that being an inert tissue, the connective tissue reveals a dynamic adaptation to loading in its protein components. Collagen formation as well as collagen degradation in the tendon rises with both acute and chronic loading, and every bout of exercise elevates collagen formation for 2-3 days. Thus connective tissue can easily be trained with resting days in between. Data suggests that a gender difference exists with regards to tendon adaptation to exercise, in that females respond less than males with regards to a rise in collagen formation after exercise. It is suggested that estrogen may contribute to a diminished collagen synthesis response in females, and maybe the effect is exerted via Insulin like growth factor.l (IGF-1).